Literature Review on the Application of International Classification of Functioning, Disability and Health for Children and Adolescents around the World and in Russian Federation - Vyacheslav V. Yazev; Dina S. Rusinova; Alexey S. Bezymyanniy (Педиатрическая фармакология)
Integration of the International Classification of Functioning, Disability and Health into the real practice of medical and social rehabilitation institutions is one of the tasks of the World Health Organization. Thus, collection of data on disability via this classification, creation of software and mobile applications for its implementation in practice will improve rehabilitation's quality and accessibility. In general, it is crucial for creation of scientific framework for health indicators and treatment outcomes assessment; for creation of common language to describe health indicators to improve understanding between health professionals, researchers, and people with disabilities; for providing information to rehabilitation-related professionals in different countries; for providing coding scheme for health information systems (including children and adolescents).